Effect of Steroids and Black Seed Oil on Hydrogen PeroxideConcentration and pH of Expired Breath Condensate inAsthmatic Patients - MoHamed Al-Samarai, Abdul Ghani; Hamed Al Obaidy, Amina (Tikrit Journal of Pharmaceutical Sciences, 2023)
Asthma is a chronic inflammatory disease of airway, with increased worldwide prevalence. This study was conducted the for evaluation the effect of different treatment regimens on expired breath condensate hydrogen peroxide concentration and pH. Patients and methods: Thirty two patients ( 17 male, 15 female), with asthma were examined during exacerbation. Asthma was diagnosed according to American Thoracic Society Criteria. The pH level was increased significantly following treatment with prednisolone. In addition, expired breath condensate hydrogen peroxide in patients with acute attack reduced significantly (P<0.0001) following treatment with prednisolone. Black seed oil treatment reduced expired breath condensate H202 concentration from 1.29 µM (95% CI, 1.08-1.50) as baseline values to 0.56 µM (95% CI, 0.45-0.67) following treatment. Furthermore, pH of expired breath condensate increased from 5.54 (95% CI, 4.97-6.11) at baseline to 6.8 (95% CI, 6.28-7.32) following treatment course of back seed oil. Thus the treatment course of black seed oil significantly reduced expired breath condensate H202 concentration (P< 0.0001) and increased exhaled pH (P< 0.0 l ). For the groups that were treated with oral prednisolone or black seed oil, there were a highly significant inverse correlation among expired breath condensate H202 with pH, Exhaled H202 with FEVl predicted percent and positive correlation for exhaled pH with FEY 1 predicted percent. Steroids and back seed are with activity to reduce expired breath condensate hydrogen peroxide concentration and pH. This may indicate that they may be used for asthma treatment.